Proverbs are the best policy: folk wisdom and American politics - Mieder, Wolfgang, author; Utah State University Press, publisher (Colorado State University. Libraries, 2005)
Wolfgang Mieder, widely considered the world's greatest proverb scholar, here considers the role of proverbial speech on the American political stage from the Revolutionary War to the present. He begins his survey by discussing the origins and characteristics American proverbs and their spread across the globe hand in hand with America's international political role. He then looks at the history of the defining proverb of American democracy, "government of the people, by the people, for the people." Subsequent essays consider such matters as Abigail Adams's masterful use of politically charged proverbs the conversion of the biblical proverb "a house divided against itself cannot stand" into a political expression Frederick Douglass's proverbial prowess in the battle against racial injustice how United States presidents have employed proverbial speech in their inaugural addresses and the proverbial language in the World War II correspondence between Franklin Roosevelt and Winston Churchill, which sharpened their communication and helped forge bonds of cooperation. Mieder concludes with an insightful, relevant examination of the significance of the ambiguous proverb "good fences make good neighbors."
Different strokes for different folks: American proverbs as an international, national, and global phenomenon -- "Government of the people, by the people, for the people": the making and meaning of an American proverb about democracy -- "God helps them who help themselves": proverbial resolve in the letters of Abigail Adams -- "A house divided against itself cannot stand": from biblical proverb to Abraham Lincoln and beyond -- "Do unto others as you would have them do unto you": Frederick Douglass's proverbial struggle for civil rights -- "It's not a president's business to catch flies": proverbial rhetoric in presidential inaugural addresses -- "We are all in the same boat now": proverbial discourse in the Churchill-Roosevelt correspondence -- "Good fences make good neighbors": the sociopolitical significance of an ambiguous proverb.
Keywords: Proverbs, American; Proverbs -- Political aspects -- United States; Rhetoric -- Political aspects -- United States; Politicians -- United States -- Language; United States -- Politics and government -- Miscellanea; United States -- Politics and government -- Quotations, maxims, etc.